Corpies: Bisnis Kreatif Pemanfaatan Sampah Kaleng dan Kertas Menggunakan Teknik Lukis Sebagai Usaha Meningkatkan Nilai Benda Bekas Pakai - Joni Agung Sudarmanto (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: In this modern era, handmade products are increasingly popular because people have begun to appreciate art. SMEs have many ways to grow with many government facilities and exhibitions that support handmade products. This is a positive sign for domestic products to be more prominent. Products that raise social issues also get more attention from the public, one of which is environmental issues. Behind the consumptive culture of humans, there are problems that they create, one of the most visible is the amount of waste. To overcome this problem, innovations were created to process consumption waste into usable products that have more economic value than just being recycled. "Corpies" business target is to process waste into reusable objects. This business focuses on producing products with painting techniques that are also become its trademark. The products produced include painting cans, stools, painting cutting boards, painting totebag, painting shoes. The method used in creating this business is in accordance with the business development timeline which consists of 9 flows starting from the collection of raw materials, the cleaning process of raw materials, to the documentation and marketing process of the product. This business also engage the participation of the surrounding community in its production so that it is expected to create a positive impact for the community, one of which is creating a new culture, such as collecting used cans, so that they can be reused and produced into high-value products. Keywords: creative business, trash cans and paper, painting techniques, corpies Abstrak: Di era modern, produk buatan tangan semakin digemari karena masyarakat sudah mulai menghargai karya seni. UKM memiliki banyak cara berkembang dengan banyaknya fasilitas dari pemerintah dan pameran yang mendukung produk buatan tangan. Ini menjadi pertanda positif bagi produk dalam negeri untuk semakin menonjol. Produk yang mengangkat isu sosial juga mendapatkan perhatian lebih dari masyarakat, salah satunya isu lingkungan. Dibalik budaya konsumtif manusia, terdapat masalah yang mereka ciptakan, salah satunya adalah menumpuknya sampah. Untuk mengatasi masalah tersebut, diciptakan inovasi untuk mengolah sampah hasil konsumsi menjadi produk layak pakai yang lebih bernilai ekonomi daripada sekedar didaur ulang. Target bisnis “Corpies” adalah mengolah sampah menjadi benda yang dapat dipakai kembali. Bisnis ini fokus memproduksi produk dengan teknik lukis yang menjadi ciri khasnya. Produk yang diproduksi diantaranya adalah kaleng lukis, stool, talenan lukis, tote bag lukis, sepatu lukis. Metode yang digunakan dalam menciptakan bisnis ini sesuai dengan alur pengembangan bisnis yang terdiri dari 9 alur yang dimulai dari pengumpulan bahan baku, pembersihan bahan baku, hingga proses dokumentasi dan pemasaran. Bisnis ini turut mengajak partisipasi masyarakat sekitar dalam produksinya sehingga diharapkan dapat menciptakan dampak positif bagi komunitas, salah satunya adalah menciptakan budaya baru mengumpulkan kaleng bekas untuk digunakan kembali dan diproduksi menjadi produk bernilai jual tinggi. Kata kunci: bisnis kreatif, sampah kaleng dan kertas, teknik lukis, corpies